2016
DOI: 10.1111/1745-9125.12109
|View full text |Cite
|
Sign up to set email alerts
|

Family Matters: Effects of Family Members’ Residential Areas on Crime Location Choice*

Abstract: According to crime pattern theory, offenders are likely to select crime locations within their awareness space. Previous studies have shown that offenders often commit crimes within their current and former residential areas and in areas they previously targeted. However, offenders’ awareness spaces obviously consist of more locations that potentially influence their crime location choices. This study examines the importance of the residential areas of offenders’ family members. Most offenders visit their fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 29 publications
4
37
0
2
Order By: Relevance
“…Indeed, some location choice research has suggested that offenders are much more likely to offend within their own awareness space than elsewhere. Arguing that for various reasons offenders might still be familiar with their former areas of residence, it has been demonstrated that they are more likely to offend near their former homes than elsewhere (Bernasco and Kooistra 2010;Lammers et al 2015;Menting et al 2016). It has also been established that they are more likely to offend near the homes of family members (Menting et al 2016).…”
Section: Distance and Awareness Spacementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, some location choice research has suggested that offenders are much more likely to offend within their own awareness space than elsewhere. Arguing that for various reasons offenders might still be familiar with their former areas of residence, it has been demonstrated that they are more likely to offend near their former homes than elsewhere (Bernasco and Kooistra 2010;Lammers et al 2015;Menting et al 2016). It has also been established that they are more likely to offend near the homes of family members (Menting et al 2016).…”
Section: Distance and Awareness Spacementioning
confidence: 99%
“…The census unit was chosen as the spatial unit of analysis because census units have a size similar to those in comparable studies (Bernasco and Block 2009;Clare et al 2009;Menting et al 2016), because census units are approximately equally sized, and because in the study area they are relatively homogenous in terms of population composition. In addition, a practical advantage is that the use of census units does not force us to estimate spillover effects (effects of attributes of nearby units on crime in a focal unit) which is a requirement if small units of analysis are used, such as census blocks or street blocks (Bernasco et al 2013; Groff and Lockwood 2014).…”
Section: Study Area and Spatial Unit Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout this paper we refer to these entities as 'neighborhoods'. The neighborhoods in this study are similarly constructed to the areas used in most previous discrete spatial choice studies and are comparable or smaller in size (e.g., Lammers et al 2015;Menting et al 2016). On average, the 193 residential neighborhoods have a population of 1287 residents (standard deviation [sd] = 1299), 717 residences (sd = 785) and cover an area of 0.79 (sd = 1.00) square kilometers.…”
Section: Neighborhood Datamentioning
confidence: 99%
“…Although researchers previously studied soccer stadiums' immediate criminogenic effects and demonstrated that crime is elevated around soccer stadiums on game days (e.g., Kurland et al, 2014a, Kurland et al, 2014b, they did not establish that it is indeed soccer game attendees who are responsible for this temporary increase in crime. In fact, a variety of potential offenders could commit non-game day property crime in the stadium's environment, including stadium attendees delaying their exploitation of previously encountered criminal opportunities but also current and previous area residents (Bernasco, 2010, Bernasco andKooistra, 2010), family members of area residents (Menting et al, 2016), and repeat offenders (Lammers et al, 2015). While residents, their family members, or offenders returning to a previous offence location will have committed some of the offences in the stadium's area, they are unlikely to be responsible for all of the property crimes recorded in the 18-months prior to the stadium's closure.…”
Section: Conclusion and Discussionmentioning
confidence: 99%